Dogs as a possible animal reservoir for leishmaniasis in Dickwella, Sri Lanka - Abayaweera, Charani A; Siriwardana, Yamuna; Abeywardana, T J; Rathnayaka, R M U K; Kumarasinghe, H G C Nuwan; Karunaweera, Nadira D (University of Colombo, 2010)
Leishmaniasis is now recognized as an endemic disease in Sri Lanka. Infection caused by Leishmania spp. is known to affect both humans and animals, including domestic dogs. Detection of an animal reservoir is important to understand transmission dynamics and to formulate control strategies. By testing for antibody response; past infections and asymptomatic disease can be detected. rK39 is a L.donovani specific antigen to which the visceralizing infection can exert a serological response